Vertical MoS2/hBN/MoS2 interlayer tunneling field effect transistor. (December 2016) - Srivastava, Ashok; Fahad, Md S.
Highlights: Interlayer tunnel transistor of molybdenum disulfide and hex-boron nitride has been proposed. Current transport has been modeled analytically. Low power operation is obtained at a subthreshold slope near 60 mV/decade. At 1.2 V the proposed device provides an operating frequency close to 19 THz. Abstract: Gate induced interlayer tunneling field effect transistor (iTFET) is studied analytically considering vertical heterostructure of boron nitride (BN) layer sandwiched between two monolayers of molybdenum disulfide (MoS2 ). The device structure in comparison to recently reported work shows subthreshold slope close to 60 mV/decade and operation at upper GHz.